2022
DOI: 10.1186/s12931-022-02263-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of miRNA-34a regulated Krüppel-like factor 4 expression in hyperoxia-induced senescence in lung epithelial cells

Abstract: Background Premature infants, subjected to supplemental oxygen and mechanical ventilation, may develop bronchopulmonary dysplasia, a chronic lung disease characterized by alveolar dysplasia and impaired vascularization. We and others have shown that hyperoxia causes senescence in cultured lung epithelial cells and fibroblasts. Although miR-34a modulates senescence, it is unclear whether it contributes to hyperoxia-induced senescence. We hypothesized that hyperoxia increases miR-34a levels, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Although type II alveolar cells account for a very small percentile of senescent cells, these cells contribute to hyperoxic lung injury via paracrine SASP factors. 7 , 39 In fact, the majority (92%) of 5-dodecanoylaminofluorescein di- β -D-galactopyranoside (C 12 FDG; a substrate of SA- β -gal) positive cells were lung macrophages. These macrophages also highly express the senescence biomarkers B2M (encoding β 2-microglobulin) 40 and Plaur (encoding uPAR) 10 as well as SASP factors, further confirming that these macrophages are senescent.…”
Section: Abnormally Induced Senescence In Perinatal Lung Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although type II alveolar cells account for a very small percentile of senescent cells, these cells contribute to hyperoxic lung injury via paracrine SASP factors. 7 , 39 In fact, the majority (92%) of 5-dodecanoylaminofluorescein di- β -D-galactopyranoside (C 12 FDG; a substrate of SA- β -gal) positive cells were lung macrophages. These macrophages also highly express the senescence biomarkers B2M (encoding β 2-microglobulin) 40 and Plaur (encoding uPAR) 10 as well as SASP factors, further confirming that these macrophages are senescent.…”
Section: Abnormally Induced Senescence In Perinatal Lung Diseasesmentioning
confidence: 99%
“… 53 We recently reported that miRNA-34a contributes to hyperoxia-induced senescence in cultured lung epithelial cells. 39 Nevertheless, further study is warranted to investigate whether these signaling pathways participate in the development of alveolar and vascular simplification seen in bronchopulmonary dysplasia by modulating cellular senescence.…”
Section: Abnormally Induced Senescence In Perinatal Lung Diseasesmentioning
confidence: 99%
“…Li et al [ 33 ] studied the damages caused by ethanol in human vascular diseases; the results showed that doxycycline restored the level of aging-related proteins such as LMNB1 by reducing the extent of mTOR and NF-κB activation, thus alleviating ethanol-induced inflammation and aging. By observing the changes of mouse lung epithelial cells and primary human small airway epithelial cells after treatment with a high concentration of oxygen (95% O 2 /5% CO 2 ) or air (21% O 2 /5% CO 2 ) for 24 h. Maeda et al [ 34 ] found that high oxygen concentration induced senescence by increasing the level of miR-34a-5p. Moreover, LMNB1 gene deletion increased p21 gene expression.…”
Section: Lmnb1 and Cancer Senescencementioning
confidence: 99%